COVID-19 Vaccine Acceptance and Its Associated Factors Among Young Adults - Regmi, Shruti; Subedi, Sanchita; Datheputhe, Parbati; Rai Koirala, Sita (Journal of College of Medical Sciences-Nepal, 2024)
Background COVID-19 pandemic, which has rapidly spread throughout the globe in several waves and mutations, was initially identified in Wuhan, China, in late 2019. Vaccines against this deadly virus were developed quickly in about a year. Despite the availability of vaccines, acceptance of the vaccines among the general population is influenced by various factors and are important to be identified for a successful vaccination program. The objective of this study was to evaluate the COVID-19 vaccine acceptance among young adults and its associated factors. Methods Nepalese young adults were surveyed online using a descriptive cross-sectional study approach. A bilingual, self-administered questionnaire consisting of six parts-socio-demographic information, health-related information, knowledge and attitude/ beliefs about COVID-19, perceived threat to COVID-19, beliefs about COVID-19 vaccination, and vaccine acceptability was used to collect data. The collected data was analysed using SPSS version 20. Results Out of the 467 participants surveyed, most of them (94.2%) were willing to take the vaccine. Among them, 80.5% were willing to take it immediately. The main reason for COVID-19 vaccine refusal was because of doubt about the safety of the COVID-19 vaccine. The regression results showed that healthcare-related professionals/students and perceived benefits of the COVID-19 vaccine were significantly associated with vaccine acceptance. Conclusions This study reflected the high acceptance of COVID-19 vaccination among Nepalese adults during the pandemic. Concerned authorities and health professionals should emphasize addressing concerns about vaccine safety and disseminating information about the benefits of vaccines to overcome vaccine hesitancy.